Pembangunan sistem maklumat kawalan kadaster secara atas talian - Keling, Noraidah (2007)
Nowadays, science and technologies have revolutionized many Geomatic disciplines. The most significant change that IT has brought about is the shift from conventional analogue data access to digital data and consequently the introduction of the concept of online digital database. These had lead to the concept and implementation of the Coordinated Cadastral System (CCS) for Malaysia. The usage of cadastral data control in CCS implementation is very important because all the measurement and cadastral control will be established according to that cadastral control datum. The objectives of the study are to develop Online-Based Cadastral Control Information System (CCIS) and to analyze the effectiveness of the system. Results from the research include e-form, e-commerce, interactive map, information of spatial and attribute data. The dataset used in this research are GPS station information, topography data, and digital cadastral database for state of Malacca. The development of this research involves several phases such as data gathering, physical design and user interface development. ArcIMS software was used in this research. The development of Online-Based CCIS is one of the initiatives to shift to E - Government. Online-Based Cadastral Control Information System can be an alternative mechanism for more effective and efficient cadastral control information access and management. This system provides a guideline for survey community especially for Department of Survey and Mapping Malaysia (DSMM).